Redescription and validity of Formosania gilberti Oshima, 1919 (Cypriniformes: Balitoridae), an endemic hillstream loach from Taiwan - Yeh, Ming-Fon; Li, Hsien-En; Han, Chiao-Chuan; Chen, I-Shiung (Zootaxa, 2024)
For over a century, only one species of Formosania has been recognised in Taiwanese waters. However, through the use of mitogenomic analyses and the identification of morphological differences, an endemic balitorid loach was revalidated and redescribed based on specimens herein of northern Taiwan. Formosania gilberti Oshima, 1919 was previously mistreated as a junior synonym of F. lacustris (Steindachner, 1908), but the two can be clearly differentiated by their vertebral counts (26+11 vs. 26+12) and body marking patterns (intensely mottled with vermicular markings vs. cloud-like blotches or brown and blotchless). Furthermore, mitogenomic analyses also showed high intra-specific diversity among Formosania loaches in Taiwan, which not only supports F. gilberti as a valid species but also hints the presence of a species complex distributed in western Taiwan.